Natural Environment and Economic Growth. The Case of Developed and Developing Countries - Morales-Urrutia, Ximena; Núñez-Naranjo, Aracelly; Álvarez, Elsy; Yánez, Evelin (Journal of Posthumanism, 2025)
Background: The objective of the research was to identify the relationship of the elements of the natural environment with Economic Growth in developed (G7) and developing (LAIA) countries. Methods: A Spearman correlation analysis was performed to identify the key factors impacting economic growth in both groups of countries. Results: The results show that, in developed countries, the main determinants of economic growth are related to polluting gas emissions, forest cover, land use and environmental conservation initiatives. In contrast, in developing countries, emissions and exposure to air pollution emerge as predominant factors affecting economic dynamism, reflecting greater vulnerability to environmental impacts. Conclusions: The natural environment plays a more significant role in the economic growth of developed countries, due to its institutional and technological capacity to implement policies aimed at conservation and environmental sustainability. In contrast, in developing countries, institutional conditions and efficient management of natural resources become key factors. This highlights the need to strengthen regulatory frameworks and increase investment in pollution mitigation strategies, as keyways to foster more prosperous and sustainable economic development.